2016
DOI: 10.4238/gmr.15038585
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic diversity and structure of Phragmites australis from local habitats of the Songnen Prairie using amplified fragment length polymorphism markers

Abstract: ABSTRACT. The genetic and epigenetic diversity and structure of naturally occurring Phragmites australis populations occupying two different habitats on a small spatial scale in the Songnen Prairie in northeastern China were investigated by assessing amplified fragment length polymorphisms (AFLPs) and methylation-sensitive amplified polymorphisms (MSAPs) through fluorescent capillary detection. The two groups of P. australis were located in a seasonal waterlogged lowlying and alkalized meadow with a pH of 8-8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(43 reference statements)
2
4
0
Order By: Relevance
“…AGD and PPL values were in line with those observed for other conspecific populations in Italy and Europe (Coppi et al, 2018;Lambertini et al, 2008). Consistently, most of the genetic variation resided within rather than among sampling plots and sites, confirming previous studies on phylogeographic relationships in common reed stands on local to narrow range scales (Coppi et al, 2018;Lambertini et al, 2008;Qiu et al, 2016). Indeed, the high local genetic diversity observed for P. australis agrees with previous evidence, and it seems directly connected with the ecological and physiological characteristics of the species (Gao et al, 2012;Richards et al, 2012).…”
Section: Genetic Structure and Traits Variationsupporting
confidence: 90%
“…AGD and PPL values were in line with those observed for other conspecific populations in Italy and Europe (Coppi et al, 2018;Lambertini et al, 2008). Consistently, most of the genetic variation resided within rather than among sampling plots and sites, confirming previous studies on phylogeographic relationships in common reed stands on local to narrow range scales (Coppi et al, 2018;Lambertini et al, 2008;Qiu et al, 2016). Indeed, the high local genetic diversity observed for P. australis agrees with previous evidence, and it seems directly connected with the ecological and physiological characteristics of the species (Gao et al, 2012;Richards et al, 2012).…”
Section: Genetic Structure and Traits Variationsupporting
confidence: 90%
“…When divergence occurred, the uHe index was preferred because of the limited number of individuals from each group (Nei, 1978). Consistent with most previous epigenetic studies of natural population differentiation (Choi, Roy, Park, & Kim, 2016; Foust et al., 2016; Kim, Im, & Nkongolo, 2016; Qiu et al., 2016; Schulz et al., 2014), more epigenetic variance existed within groups than genetic variance. One general explanation for this is that a population with limited genetic diversity, especially after genetic drift, can extend its ecological niche through epigenetic variation, which is potentially sensitive to environmental stimulation (Richards, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some heritable traits and ecophysiological differences in the common reed may contribute to invasion success but hitherto cannot be explained by particular genetic lineages (Mozdzer, Brisson, & Hazelton, 2013). However, very few investigations of natural epigenetic variation of P. australis have been reported, and previous studies were conducted just at a small scale such as in midcoast Maine (Spens & Douhovnikoff, 2016) and in the Songnen Prairie of China (Qiu, Jiang, & Yang, 2016). The understanding of potential epigenetic mechanisms in the invasion of P. australis is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the north of Songnen Plain, the water content is relatively abundant and temperature becomes the limit factor affecting the growth of Phragmites australis. It is reported that low temperatures caused by precipitation can limit the absorption of nutrition by plant roots and thus prohibits Phragmites australis growth of marshes [64]. In the south of Songnen Plain, the growth of Carex was mainly affected by the precipitation due to limited water content in the seasonal marsh regions.…”
Section: The Correlations Between Climate Variables and Ndvi Of The S...mentioning
confidence: 99%